Islamic Entrepreneurship Research Trends in A Bibliometric Analysis Based on the Scopus Database (2010-2024) - Haris, Muhammad; Abroza, Ahmad; Ardiansyah, Iwan; Syahrudin, M.; Umam, Akmalul (Journal of Islamic Economic and Business Research, 2025)
This study aims to conduct a bibliometric review of the scientific literature on Islamic Entrepreneurship from 2010 to early 2024. By applying strict inclusion and exclusion criteria and using quantitative techniques, this study identified and analyzed 36 articles published in 29 relevant journals. Data were retrieved from the Scopus database and analyzed using the Biblioshiny application to describe publication trends, citations, and author collaborations. The results show that research on Islamic Entrepreneurship has grown significantly, with a peak in publications in 2021 and 2022. There are some of the most influential writers who have made significant contributions to the understanding of Islamic entrepreneurship. Malaysia and Indonesia emerged as major contributors, reflecting the high interest in this topic in countries with the largest Muslim populations. The thematic map reveals the evolution of focus from general topics to specific issues such as innovation and SMEs in the Islamic context. Future research agendas are suggested to explore the role of digital technologies, Islamic financing models, social entrepreneurship, and the impact of government policies. These findings emphasize the importance of Islamic Entrepreneurship in a global context and provide a basis for further research in addressing the challenges and opportunities faced by Muslim entrepreneurs.